2022
DOI: 10.3390/jfb13020057
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Chemical Characterization of Biomineralized Collagen with Different Microstructures

Abstract: Mineralized collagen is the basic unit in hierarchically organized natural bone with different structures. Polyacrylic acid (PAA) and periodic fluid shear stress (FSS) are the most common chemical and physical means to induce intrafibrillar mineralization. In the present study, non-mineralized collagen, extrafibrillar mineralized (EM) collagen, intrafibrillar mineralized (IM) collagen, and hierarchical intrafibrillar mineralized (HIM) collagen induced by PAA and FSS were prepared, respectively. The physical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…The different I-EMC samples exhibit similar infrared spectral patterns. Firstly, the absorption peaks corresponding to the triple helical structure of collagen are present, indicating that the triple helical structure of collagen is well-preserved after mineralization ( Du et al, 2022 ). In the biomimetic mineralization process, calcium phosphate ions first aggregate to form ACP, which then deposits within the collagen fibers and eventually transforms into poorly crystalline hydroxyapatite and hydroxyapatite crystals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The different I-EMC samples exhibit similar infrared spectral patterns. Firstly, the absorption peaks corresponding to the triple helical structure of collagen are present, indicating that the triple helical structure of collagen is well-preserved after mineralization ( Du et al, 2022 ). In the biomimetic mineralization process, calcium phosphate ions first aggregate to form ACP, which then deposits within the collagen fibers and eventually transforms into poorly crystalline hydroxyapatite and hydroxyapatite crystals.…”
Section: Resultsmentioning
confidence: 99%
“…However, despite scientists around the world putting in tremendous effort, this high-level biomimetic preparation method has not yet achieved a breakthrough ( Chen et al, 2023 ). Studies have demonstrated that, when employing the PILP method, the surface of IMC shows deposits of calcium phosphate particles, indicating the occurrence of extrafibrillar mineralization, i.e., I-EMC ( Hu et al, 2016 ; Du et al, 2022 ). The preparation of I-EMC involves three essential components: Type-I collagen, minerals, and non-collagen analogs (NCP) ( Oosterlaken et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The P and Ca elements throughout the mineralization process changed the calcium-deficient HA and apatite crystals into amorphous calcium phosphate (ACPs). 18 The scissor-like bend vibration of water molecule H 2 O causes the band at 1637 cm –1 . Similar to this, the Si–O and Si–O–Si linkage vibrations’ asymmetric stretching can be seen in the band at 1097 and 802 cm –1 , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that periodic fluid shear stress (FSS) can replace polyacrylic acid (PAA) and induce highly-arranged IMC and HIMC in the presence of TPP [ 72 , 73 ]. Moreover, periodic FSS has been shown to improve the hydrophilicity, enzymatic stability, and crystal conversion of mineralized collagen [ 74 ]. In addition, other substances such as polyamide dendritics [ 75 , 76 ], sodium alginate [ 77 ], chitosan [ 21 , 53 ], sodium citrate [ 78 ], succinic acid [ 79 ], alkaline phosphatase (ALP) [ 80 ], and osteopontin (OPN) [ 81 ] have also been found to regulate the process of biomimetic mineralization in vitro .…”
Section: Biomimetic Collagen Mineralizationmentioning
confidence: 99%
“…Variations in preparation methods, material sources, and processing parameters can lead to changes in the nanostructure of MC [ 74 ]. These changes, in turn, affect the mechanical properties, degradability, and bone-inducing ability of MC both in vitro and in vivo .…”
Section: Biomimetic Collagen Mineralizationmentioning
confidence: 99%